A simple method for detecting very small changes in capacitance or inductance. (July 2020) - Deguchi, Mikio
Abstract: A simple method for detecting very small changes in capacitance or inductance is presented. In the circuit used in the proposed method, which employs LC resonance, the phase of the output signal sharply and monotonically changes by about 180° around the resonance frequency. When the capacitance or inductance changes slightly, the resonance frequency shifts accordingly. This change can be sensitively detected as a phase shift of the output signal by applying a fixed frequency signal to the circuit near the resonance frequency. The circuit used for detection is entirely composed of general-purpose electronic components and does not use special function devices. This method can be applied in various practical contexts, for example, object detection, proximity sensing, monitoring material properties, and electric capacitance tomography.